Communication and innovation of the Church in the audiovisual media. The video messages of Pope Francis - Cartes-Barroso, Manuel Jesús (2023)
The interest of religions in communicating in the new virtual environments has led to the emergence in recent years of multimedia initiatives that seek to inform and bring their message to many people. Such is the case of 'The Pope Video', a project of the Pope's Worldwide Prayer Network (Apostleship of Prayer) born in 2016 and supported by Vatican Media, with the purpose of launching the Holy Father's monthly intentions on a global level, through the dissemination of video messages on the web and social networks. The aim of this research is to analyze this project of the Church in the audiovisual media and as a methodology we have carried out a quantitative and qualitative content analysis of the videos (n=75) published between 2016 and 2021, in order to understand its evolution in terms of the themes highlighted, the quality and use of images and sounds, the audiovisual production and its internal structure. These are digital videos with good audiovisual production and editing, as well as a professional treatment of image and sound. The Pope is the protagonist of these videos, in which he reflects on various topics of social and human interest. Francis' naturalness and his approachable language, together with the strategic use of audiovisuals to reach his followers in the present digital age, make 'The Pope Video' a good example of direct communication between a religious leader and the faithful. A paradigm of innovation by the Catholic Church in audiovisual communication.